Post-translational modifications regulate signalling by Ror1 - Kaucká, M; Krejčí, P; Plevová, K; Pavlová, S; Procházková, J; Janovská, P; Valnohová, J; Kozubík, A; Pospíšilová, S; Bryja, V (Acta physiologica (Oxford, England), 2011)
AIM: In this study, we analysed the post-translational modification of receptor tyrosine kinase-like orphan receptor (Ror1). Ror1 is highly upregulated in B cells of patients with chronic lymphocytic leukaemia (CLL). Molecularly, Ror1 acts as the Wnt receptor in the non-canonical Wnt pathway. METHODS: The level of Ror1 glycosylation in HEK293 cells and in primary human CLL cells was analysed by treatment of inhibitors interfering with different steps of glycosylation process and by direct treatment of cell lysates with N-glycosidase. Ror1 ubiquitination was determined by ubiquitination assay. Functional consequences of post-translational modifications were analysed by immunohistochemistry and by analysis of cell surface proteins. Differences in Ror1 glycosylation were confirmed by analysis of 14 samples of B cells from CLL patients. RESULTS: We demonstrate that Ror1 is extensively modified by N-linked glycosylation. Glycosylation produces several variants of Ror1 with electrophoretic migration of approx. 100, 115 and 130 kDa. Inhibition of glycosylation interferes with cell surface localization of the 130-kDa variant of Ror1 and prevents Ror1-induced formation of filopodia. Moreover, we show that 130-kDa Ror1 is mono-ubiquitinated. Furthermore, individual CLL patients show striking differences in the electrophoretic migration of Ror1, which correspond to the level of glycosylation. CONCLUSION: Our data show that Ror1 undergoes complex post-translational modifications by glycosylation and mono-ubiquitination. These modifications regulate Ror1 localization and signalling, and are highly variable among individual CLL patients. These may suggest that Ror1 signals only in a subset of CLL patients despite Ror1 levels are ubiquitously high in all CLL patients.
Keywords: Electrophoresis, Polyacrylamide Gel; transport proteinů; lidé; průtoková cytometrie; ubikvitinace; Molecular Weight; Cricetinae; Flow Cytometry; B-lymfocyty; transfekce; Signal Transduction; Microscopy, Confocal; CHO buňky; imunohistochemie; Humans; Cricetulus; Protein Transport; Receptor Tyrosine Kinase-like Orphan Receptors; Blotting, Western; western blotting; signální transdukce; CHO Cells; Immunohistochemistry; molekulová hmotnost; HEK293 buňky; křečci praví; Glycosylation; zvířata; glykosylace; Ubiquitination; sirotčí receptory podobné receptoru tyrosinkinasy; elektroforéza v polyakrylamidovém gelu; pseudopodia; B-Lymphocytes; Animals; posttranslační úpravy proteinů; chronická lymfatická leukemie; konfokální mikroskopie; Pseudopodia; Protein Processing, Post-Translational; HEK293 Cells; Transfection; Leukemia, Lymphocytic, Chronic, B-Cell